2019
DOI: 10.1101/815241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Evaluation of the In Vitro Roles and Mechanisms of Silibinin in Reducing Pyrazinamide- and Isoniazid-Induced Hepatocellular Damage

Abstract: Tuberculosis remains a significant infectious lung disease that affects millions of patients worldwide. Despite numerous existing drug regimens for tuberculosis, Drug-Induced Liver Injury is a major challenge that limits the effectiveness of these therapeutics. Two drugs that form the backbone of the commonly administered quadruple antitubercular regimen, i.e. pyrazinamide (PZA) and isoniazid (INH), are associated with such hepatotoxicity. The problem is compounded by the lack of safe and effective alternative… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…It could also be suggested that the administration of MEL may prevent liver damage related to the maintenance of plasma membrane integrity, thereby suppressing the leakage of enzymes through membranes. Additionally, MEL may also exhibit hepatocurative activity against the hepatotoxicity induced by a combination of INH and RIF drugs [ 35 ]. Mel15 and Mel30 treatment reduced the elevation of AST and ALT activities; with MEL groups showing greater improvement than the NR group.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be suggested that the administration of MEL may prevent liver damage related to the maintenance of plasma membrane integrity, thereby suppressing the leakage of enzymes through membranes. Additionally, MEL may also exhibit hepatocurative activity against the hepatotoxicity induced by a combination of INH and RIF drugs [ 35 ]. Mel15 and Mel30 treatment reduced the elevation of AST and ALT activities; with MEL groups showing greater improvement than the NR group.…”
Section: Discussionmentioning
confidence: 99%